THE EFFECTIVENESS OF TEAMWORK TOURNAMENT IN TEACHING STUDENTS’ SPEAKING - Anam, Mukhtarul; Setyaningrum, Riya Risqi; Widyaiswara, Tiara; Sa'adah, Fitria Lailatus (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
This study aims to knowing the Effectiveness of Teamwork Tournament in teaching student’s speaking. This research used Quantitative method which is Quasi-experimental. The subject of this research was 8th grade at Mts Putra Putri Lamongan. The writer chose 8th A consisted of 17 students as the experimental class and 8th B consisted of 16 students as the control class. The data was gathered throught Pre-test and post-test. The result of this study showed from T-test the value t-table =2.039. Because t-count is greater than t-table (4.126>2.039) at significance level of 0.05. There is significant effectiveness of Teamwork Tournament learning method in teaching students’ speaking. The result of mean score for the experimental class is 84.00. and, the mean score for control class is 79.50 it was concluded that there was difference meanscore between the experimental class taught by using Teamwork Tournament and conventional class in teaching students’ speaking. So, the conclusion of this study, The Teamwork Tournament method in teaching speaking was success categories.